Water Plasma Functionalized CNTs/MnO2 Composites for Supercapacitors - Shahzad Hussain; Roger Amade; Eric Jover; Enric Bertran (The Scientific World Journal)
A water plasma treatment applied to vertically-aligned multiwall carbon nanotubes (CNTs) synthesized by plasma enhanced chemical vapour deposition gives rise to surface functionalization and purification of the CNTs, along with an improvement of their electrochemical properties. Additional increase of their charge storage capability is achieved by anodic deposition of manganese dioxide lining the surface of plasma-treated nanotubes. The morphology (nanoflower, layer, or needle-like structure) and oxidation state of manganese oxide depend on the voltage window applied during charge-discharge measurements and are found to be key points for improved efficiency of capacitor devices. MnO2/CNTs nanocomposites exhibit an increase in their specific capacitance from 678 Fg−1, for untreated CNTs, up to 750 Fg−1, for water plasma-treated CNTs.